2021
DOI: 10.1038/s41467-021-25903-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and structural basis of a lethal mouse-adapted SARS-CoV-2

Abstract: There is an urgent need for animal models to study SARS-CoV-2 pathogenicity. Here, we generate and characterize a novel mouse-adapted SARS-CoV-2 strain, MASCp36, that causes severe respiratory symptoms, and mortality. Our model exhibits age- and gender-related mortality akin to severe COVID-19. Deep sequencing identified three amino acid substitutions, N501Y, Q493H, and K417N, at the receptor binding domain (RBD) of MASCp36, during in vivo passaging. All three RBD mutations significantly enhance binding affini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 58 publications
6
76
0
Order By: Relevance
“…However, over the course of the pandemic, SARS-CoV-2 variants emerged that could infect mice. For example, variants harboring the spike mutation N501Y, which are relatively common in human patients (24.7%, CoV-GLUE-Viz, accessed on November 23 th , 2021), could infect mice ( Gu et al, 2020 ; Leist et al, 2020 ; Sun et al, 2021 ). If the progenitor of Omicron indeed evolved in a mouse species before the Omicron outbreak, we postulated that its spike protein likely adapted through increased binding affinity for mouse ACE2.…”
Section: Resultsmentioning
confidence: 99%
“…However, over the course of the pandemic, SARS-CoV-2 variants emerged that could infect mice. For example, variants harboring the spike mutation N501Y, which are relatively common in human patients (24.7%, CoV-GLUE-Viz, accessed on November 23 th , 2021), could infect mice ( Gu et al, 2020 ; Leist et al, 2020 ; Sun et al, 2021 ). If the progenitor of Omicron indeed evolved in a mouse species before the Omicron outbreak, we postulated that its spike protein likely adapted through increased binding affinity for mouse ACE2.…”
Section: Resultsmentioning
confidence: 99%
“…Coincidentally, two recent works showed that mouse-adapted SARS-CoV-2 strains MASCp6 and MASCp36, which harbored single-residue N501Y mutation and triple-residue K417N, Q493H and N501Y mutations, respectively, were capable of infecting wild-type mice. 12 , 15 The binding affinities of RBD (N501Y) and RBD (K417N, Q493H, and N501Y) to mACE2 were increased compared with the RBD of SARS-CoV-2 (G614). These works prompted us to investigate whether the natural SARS-CoV-2 variants, especially B.1.351 strain, might acquire the ability to directly infect the wild-type mice.…”
Section: Introductionmentioning
confidence: 99%
“…One is “adapting” virus to mice by serial passaging of virus in mice to enhance the binding affinity of the Spike to mACE2. 12 – 16 Another is “adapting” mice to SARS-CoV-2 viruses by introducing hACE2 in mice to facilitate the Spike-binding affinity. 17 23 However, the mouse-adapted SARS-CoV-2 strains often acquire adaptive mutations, some of which are even within RBD, which may restrict their transmission in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 primo-culture stocks used as B ( n = 1 viral strain) (EPI_ISL_4537783), Alpha ( n = 2) (EPI_ISL_4536454 and EPI_ISL_4536996), Beta ( n = 2) (EPI_ISL_4537125 and EPI_ISL_4537284), Gamma ( n = 1) (EPI_ISL_4536760), and A.27 ( n = 1) (EPI_ISL_4537460) was produced in Vero E6 cells. The supernatant were quantified with viral RNA levels and titrated by lysis plaque assay ( Gordon et al., 2020 ), aliquoted, and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 was titrated by a lysis-plaque assay as previously described ( Gordon et al., 2020 ). Briefly, Vero E6 cells were seeded onto a 12-well plate at a density of 100,000 in DMEM with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%